2002
DOI: 10.1128/mcb.22.9.2993-3002.2002
|View full text |Cite
|
Sign up to set email alerts
|

Altered p27Kip1 Phosphorylation, Localization, and Function in Human Epithelial Cells Resistant to Transforming Growth Factor β-Mediated G1 Arrest

Abstract: p27Kip1 is an important effector of G1 arrest by transforming growth factor β (TGF-β). Investigations in a human mammary epithelial cell (HMEC) model, including cells that are sensitive (184S) and resistant (184A1L5R) to G1 arrest by TGF-β, revealed aberrant p27 regulation in the resistant cells. Cyclin E1-cyclin-dependent kinase 2 (cdk2) and cyclin A-cdk2 activities were increased, and p27-associated kinase activity was detected in 184A1L5R cells. p27 from 184A1L5R cells was localized to both nucleus and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 54 publications
(86 reference statements)
3
49
0
Order By: Relevance
“…Our previous work showed that the acquisition of TGF-␤ resistance in human mammary epithelial cells was associated with altered phosphorylation, altered Cdk inhibitory activity, and cytoplasmic mislocalization of the p27 protein (15). Although p27 gene mutations are rare in human tumors, increased proteasomal degradation of p27 is observed in a number of cancers, including breast, colon, and prostate, and the reduced p27 levels are associated with poor patient prognosis (reviewed in Refs.…”
Section: Tgf-␤mentioning
confidence: 99%
“…Our previous work showed that the acquisition of TGF-␤ resistance in human mammary epithelial cells was associated with altered phosphorylation, altered Cdk inhibitory activity, and cytoplasmic mislocalization of the p27 protein (15). Although p27 gene mutations are rare in human tumors, increased proteasomal degradation of p27 is observed in a number of cancers, including breast, colon, and prostate, and the reduced p27 levels are associated with poor patient prognosis (reviewed in Refs.…”
Section: Tgf-␤mentioning
confidence: 99%
“…The first role is the inhibition of cyclin E-cdk2. The second is that p27 facilitates assembly, activation and nuclear localization of cyclin D-cdk complexes in early G1 phase (5,6). Therefore, inactivation of p27 results in cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…6 Rather complex patterns of phosphorylation were revealed in quiescent and proliferating cells by isoelectric focusing using two-dimensional electrophoresis. [35][36][37] The pattern of p27 phosphorylation differs between cell types and changes during cell cycle progression, where a significant increase in p27 phosphorylation correlates with cell cycle entry. 35,37 The β-catenin-TCF.…”
mentioning
confidence: 99%